A Way to Control Distortion of Metal Parts during Heat Treatment Process - Yuan Lu; Jinwu Kang; Haimin Long; Gang Nie; Tianyou Huang (The Minerals, Metals and Materials Society, 2012)
"The distortion of metal parts during heat treatment process is one of the main obstacles in industry to ensure high-quality work and less or no machining allowance, especially for large but thin steel castings such as heavy turbine blades. In the paper, a method is proposed to control the distortion by adjusting heat transfer coefficient of metal parts during heat treatment process. Required heat transfer coefficients can be realized by getting the metal parts into contact with various media such as water spray, insulation felt or materials with different heat conductivity. The control method based on this idea is set up and achieved. By using insulation felt and water spray to change the heat transfer coefficient during the stages of heat treatment process, the results indicate that the proper control time and vary with materials.IntroductionThe distortion of metal parts during heat treatment process is one of the main obstacles in industry to ensure high-quality work and to realize less or no machining allowance [1]. For example, the Three Gorges turbine blade’s distortion is as large as 50mm during heat treatment process. The uneven heating and cooling during heat treatment process is the main reason for distortion [2]. By adjusting heat transfer coefficient of different areas of metal parts, the heat treatment process could be controlled. The temperature variation, direct cause for distortion, could be under control. Loeser Klaus used high pressure gas to achieve uniform heat transfer during gas quenching and proposed the possibility to use ""Dynamic Quenching"" processes where the quenching severity is varied during quenching by stepwise control of either gas velocity or gas pressure [3]. Li Zhichao also suggested minimizing distortion by marking a component into several areas and imposing different heat transfer coefficients on each area [4]. Heat transfer coefficient can be controlled by getting the metal parts into contact with different media such as water spray, insulation felt, air or different heat conduction materials. In addition, the exact time to adjust the heat transfer coefficient is another factor for distortion. A method is presented in this paper by actively adjusting heat transfer coefficient for different areas of metal parts and different stages of heat treatment process to control their distortion. The corresponding experiments have been made by using different metal materials."